2020
DOI: 10.1021/acs.chemrev.0c00761
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the “Dots”: From Free Radical Lipid Autoxidation to Cell Pathology and Disease

Abstract: Our understanding of lipid peroxidation in biology and medicine is rapidly evolving, as it is increasingly implicated in various diseases but also recognized as a key part of normal cell function, signaling, and death (ferroptosis). Not surprisingly, the root and consequences of lipid peroxidation have garnered increasing attention from multiple disciplines in recent years. Here we “connect the dots” between the fundamental chemistry underpinning the cascade reactions of lipid peroxidation (enzymatic or free r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 334 publications
0
79
0
1
Order By: Relevance
“…From an analytical point of view, the measurement of oxidative stress is quite complex due to the fact that the oxidant species causing oxidative stress are very reactive and unstable and so are short lived species [ 8 , 9 ]. A direct measurement of these species can be performed in the presence of radical spin trappers for the radical species (ESR experiments) [ 10 ] or using suitable fluorescence probes which form a fluorophore when undergoing oxidation [ 2 ]. These techniques are mainly performed in in vitro conditions because their measurement requires that the spin trapper/fluorescent probe is added concomitantly to the oxidant formation.…”
Section: Oxidative Stress Biomarkersmentioning
confidence: 99%
See 3 more Smart Citations
“…From an analytical point of view, the measurement of oxidative stress is quite complex due to the fact that the oxidant species causing oxidative stress are very reactive and unstable and so are short lived species [ 8 , 9 ]. A direct measurement of these species can be performed in the presence of radical spin trappers for the radical species (ESR experiments) [ 10 ] or using suitable fluorescence probes which form a fluorophore when undergoing oxidation [ 2 ]. These techniques are mainly performed in in vitro conditions because their measurement requires that the spin trapper/fluorescent probe is added concomitantly to the oxidant formation.…”
Section: Oxidative Stress Biomarkersmentioning
confidence: 99%
“…The general process of LPO consists of three stages: initiation, propagation, and termination [ 2 ]. Hydroxyl and hydroperoxyl radicals are the most powerful initiators of LPO.…”
Section: Lipid Peroxidation In Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, iron could also cause ferroptosis via other pathways expect for Fenton chemistry, such as iron redox couple-catalyzed oxidation of unsaturated lipids [9 , [13] , [14] 15] . Several studies have reported iron-induced oxidation in liposomes and iron loaded liposome triggered lipid peroxide for ferroptosis therapy [15 17] .…”
Section: Introductionmentioning
confidence: 99%